The effect of basketball footwear on the vertical ground reaction force during the landing phase of drop jumps - Jesús Cámara Tobalina (Revista de Psicología del Deporte, 2013)
Even though the aetiology of overuse injuries is multifactorial, repetitive impacts and insufficient cushioning have been pointed out as themain causes of injury. These impacts are characterized at the vertical ground reaction force by 2 peaks. The first corresponds to the landing of the forefoot (F1) and the second (F2), associated to the production of injuries. Basketball footwear, due to its design and materials, might also help cushion the impact of the foot with the ground. Nevertheless, it has not been ascertained whether this footwear reduce the impact of the foot with the ground. The aim was to determine the effect of basketball footwear on the vertical ground reaction force during the landing phase of drop jumps. Thirteen students of the University of the B. Country (age = 21.54 ± 1.12 yr; body mass = 71.83 ± 8.15 kg; height = 177 ± 7 cm) took part. They all were required to perform 3 drop landings (DL) from 30 cm (DL30) and 60 cm (DL60) high in 2 different conditions: with basketball footwear or with running footwear. Resting period between jumps was 60-90 s. We presented data from 30 cm, 2.27 ± 1.07, v (m. s–1) with basketball footwear and 2.49 ± 1.23 v (m • s–1) with the alternative one. In F2, the analysis concluded that the parameter in both, 30 cm and 60 cm, presented differences between basketball and running sport shoes (6.20 ± 1.93 vs. 5.72 ± 1.79 Bw; 9.34 ± 2.16 vs. 8.27 ± 2.07 Bw). The F2 values recorded with running shoes were lower than those recorded when wearing basketball footwear (DL30: 11.13% DL60: 11.46%). The fore and rear foot impacts and loading rate are higher when jumping from 60 cm under both conditions. The F2 was the only statistically distinctive parameter between shoe conditions from both heights with lower values for non- basketball footwear.